Pengaruh Kepemimpinan Autentik CEO Terhadap Komitmen Afektif dan Symmetrical Internal Communication: Studi pada Perusahan Plywood Temanggung - Chike Amanda Selsa; Harmanda Berima Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the influence of CEO authentic leadership on symmetrical internal communication and employee affective commitment in the context of a plywood company. This research uses quantitative methods by distributing questionnaires to 190 plywood company workers around Temanggung. The results of analysis using regression analysis show that authentic leadership has a positive effect on affective commitment and symmetrical internal communication in the context of plywood companies in Temanggung.